A light–emission textile device: conformal spray-sintering of a woven fabric electrode. (20th May 2016) - Lanz, T; Sandström, A; Tang, S; Chabrecek, P; Sonderegger, U; Edman, L
Abstract: We report on the realization of an ultra-flexible, light-weight and large-area emissive textile device. The anode and active material of a light-emitting electrochemical cell (LEC) were deposited by conformal spray-coating of a transparent fabric-based electrode, comprising a weave of fine Ag-coated Cu wires and poly(ethylene naphthalene) monofilament fibers embedded in a polyurethane matrix. The yellow-emitting textile featured low turn-on voltage (5 V), high maximum brightness (>4000 cd m −2 ), good efficiency (3.4 cd A −1 ), and reasonable lifetime (180 h at >100 cd m −2 ). Uniform emission to the eye was attained from thin and highly flexible textiles featuring a large emission area of 42 cm 2, without resorting to planarization of the partially wavy-shaped (valley-to-peak height = 2.7 μ m) fabric electrode. The key enabling factors for the functional emissive textile are the characteristic in situ electrochemical doping of LEC devices, the 'dry' spray-sintering deposition of the active material, and the attractive mechanical, electronic and optical properties of the fabric-based electrode.